P‐35: Human Visual System Inspired Artifact Reduction in Projector Compensation. Issue 1 (29th May 2019) - Sankar, Vignesh; Fieguth, Paul; Lamm, Mark
Abstract : Projection onto an arbitrary surface requires radiometric compensation to correct for distortions caused by the colors and texture of the underlying surface. Radiometric compensation modifies the projector input image with respect to the projection surface characteristics. Due to the limited dynamic range of any projector, the modified target image can easily go beyond the projector intensity limits, causing saturation artifacts. In this paper, a novel locally‐adaptive, spatial luminance modification framework is presented to reduce brightness/contrast demands on the projector during radiometric compensation.